2012
DOI: 10.1016/j.nuclphysa.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Gluon saturation: Survival probability for leading neutrons in DIS

Abstract: In this paper we discuss the example of one rapidity gap process: the inclusive cross sections of the leading neutrons in deep inelastic scattering with protons (DIS). The equations for this process are proposed and solved, giving the example of theoretical calculation of the survival probability for one rapidity gap processes. It turns out that the value of the survival probability is small and it decreases with energy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…11 The observable R contains the gap survival probability S. This has an intrinsic non-perturbative nature [29][30][31][32][33] In most applications it has been assumed to be an empirically determined constant depending only on the center of mass energy, although recent results have shown it should have some kinematic dependence [34,35]. Figure 6.…”
Section: Mueller-tang Jetsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The observable R contains the gap survival probability S. This has an intrinsic non-perturbative nature [29][30][31][32][33] In most applications it has been assumed to be an empirically determined constant depending only on the center of mass energy, although recent results have shown it should have some kinematic dependence [34,35]. Figure 6.…”
Section: Mueller-tang Jetsmentioning
confidence: 99%
“…This can be seen in Figures7(a) and 8(a) in the large excess of BFKL events at zero multiplicity 11. The observable R contains the gap survival probability S. This has an intrinsic non-perturbative nature[30][31][32][33][34] In most applications it has been assumed to be an empirically determined constant depending only on the center of mass energy, although recent results have shown it should have some kinematic dependence[35,36] 12. If the jet vertices are kept at leading order the general expression can be greatly simplified.…”
mentioning
confidence: 99%
“…[13][14][15] indicated that these effects strongly affect leading neutron production in pp collisions. In contrast, the absorptive corrections are predicted to be smaller in ep collisions and their effects become weaker at larger photon virtualities [6,8,13,[16][17][18]. Although the treatment of the absorptive corrections has advanced in recent years, they are still one of the main uncertainties in the study of leading neutron production in pp collisions at RHIC and LHC and ep collisions at the EIC and LHeC.…”
mentioning
confidence: 99%